Enhanced healing of critical-sized bone defects using degradable scaffolds with tailored composition through immunomodulation and angiogenesis - Juncen Zhou; Negar Akrami; Hanbo Wang; Liang Fang; Jie Shen; Cunjiang Yu; Ben Zhang; Donghui Zhu (Bioactive Materials)
The impact of orthopedic scaffolds on bone defect healing, particularly the late-stage bone remodeling process, is pivotal for the therapeutic outcome. This study applies fadditively manufactured scaffolds composed of hydroxyapatite-doped poly(lactide-co-glycolide)-b-poly(ethylene glycol)-b-poly(lactide-co-glycolide) (HA-PELGA) with varying properties to treat rat calvarial defects, elucidating their significant role in bone remodeling by modulating physiological responses. We engineered two scaffolds with different polylactic acid (PLA) to polyglycolic acid (PGA) ratio (9/1 and 18/1) to vary in hydrophobicity, degradation rate, mechanical properties, and structural stability. These variations influenced physiological responses, including osteogenesis, angiogenesis, and immune reactions, thereby guiding bone remodeling. Our findings show that the HA-PELGA(18/1) scaffold, with a slower degradation rate, supported bulk bone formation due to a stable microenvironment. Conversely, the HA-PELGA(9/1) scaffold, with a faster degradation rate and more active interfaces, facilitated the formation of a thin bone layer and higher bone infiltration. This study demonstrates these degradable scaffolds help to promote bone healing and reveals how scaffold properties influence the bone remodeling process, offering a potential strategy to optimize scaffold design aiming at late-stage bone defect healing.